Serum Prostaglandin D Synthase Level after Coronary Angioplasty May Predict Occurrence of Restenosis - Inoue, Teruo; Takayanagi, Kan; Morooka, Shigenori; Uehara, Yoshio; Oda, Hiroshi; Seiki, Kousuke; Nakajima, Hiroshi; Urade, Yoshihiro (Thrombosis and Haemostasis, 2001)
Lipocalin-type prostaglandin D synthase (L-PGDS), which is responsible for the biosynthesis of PGD2, has recently been found to be present in the atherosclerotic plaque of the human coronary artery and also to be secreted in human serum. We measured the serum L-PGDS level and compared it with the expressions of the platelet membrane surface glycoprotein and neutrophil adhesion molecule in patients undergoing PTCA. The L-PGDS level significantly decreased (P < 0.01) and the platelet surface expression of CD62P (P-selectin) significantly increased (P < 0.01) immediately after PTCA in the coronary sinus blood. Both changes were inversely correlated (R = −0.72, P < 0.001). Although the L-PGDS level in the coronary sinus blood remained equivalent to the baseline level in patients who experienced restenosis, the level increased over the baseline level (P < 0.01) at 48 h after PTCA in patients without restenosis. Neutrophil surface expression of CD11b (a subunit of Mac-1) significantly increased at 24 h (P < 0.01) to 48 h (P < 0.001) after PTCA in the coronary sinus blood in patients with restenosis but the change showed less significant in patients without restenosis. The changes in the L-PGDS level and the CD11b expression at 48 h after PTCA were inversely correlated (R = −0.55, P < 0.05). An increased serum L-PGDS level at 48 h after PTCA possibly predicts the avoidance of late restenosis. It is suggested that reduction in PGD2 synthesis triggers platelet activation and that a subsequent increase in the PGD2 synthesis suppresses inflammatory reaction at the intervention site indicated by neutrophil activation and inhibits development of restenosis. Pharmacological or biological intervention that increases endogenous PGD2 synthesis should be tested as a new strategy to prevent restenosis.
Keywords: Prostaglandin D synthase; prostaglandin D2; platelet; neutrophil; restenosis